A prospective study of fistula in ano with reference to clinicopathology, imaging and management - Saxena, Pradeep; Yadav, Sahab Singh (International Surgery Journal, 2019)
Background: The aim was to study and review clinical presentation, pathological aspects & prevalent modalities of investigation and treatment for fistula in ano. Methods: A prospective study of 90 patients of fistula in ano admitted from March 2015 to December 2016 was done. Fistulography was done as a preliminary investigation in 72 cases and MR Fistulography was done for complex and recurrent fistula (16 cases). Patients were operated and histopathology of fistula tract was done. In patients with clinical suspicion of tuberculosis smear examination of pus with ziehl neelsen staining for acid fast bacilli (AFB) and Cartridge Based Nucleic Acid Amplification Test (CBNAAT) on pus/slide was used to find out tuberculosis in patients of anal fistula. The clinical presentation, operation performed, pathological findings were recorded & a descriptive analysis was done. Results: A prospective study of 90 patients of fistula in ano admitted from March 2015 to December 2016 was done. Fistulography was done as a preliminary investigation in 72 cases and MR Fistulography was done for complex and recurrent fistula (16 cases). Patients were operated and histopathology of fistula tract was done. In patients with clinical suspicion of tuberculosis smear examination of pus with ziehl neelsen staining for acid fast bacilli (AFB) and Cartridge Based Nucleic Acid Amplification Test (CBNAAT) on pus/slide was used to find out tuberculosis in patients of anal fistula. The clinical presentation, operation performed, pathological findings were recorded & a descriptive analysis was done. Conclusions: With careful clinical evaluation, appropriate imaging studies and conventional surgical techniques anal fistula can be treated effectively with less morbidity, incontinence and recurrence.